Laparoscopic Roux-en-Y gastric bypass in super obese Göttingen minipigs - Birck, Malene M (e-Century Publishing Corporation, 2013)
Background: The specific mechanisms behind weight loss and comorbidity improvements in obese patients after Roux-en-Y gastric bypass (RYGBP) are still poorly understood. The aim of this study was to establish and evaluate the feasibility of a long-term survival RYGBP model in super obese Göttingen minipigs in order to improve the translational potential relative to current animal models. Methods: Eleven Göttingen minipigs with diet-induced obesity underwent laparoscopic RYGBP and were followed up to 9 months after surgery. Intra- and post-operative complications, body weight (BW), food intake and necropsy data were recorded. Results: Five minipigs survived without complications to the end of the study. Four minipigs developed surgical related complications and were euthanized while two minipigs died due to central venous catheter related complications. BW and food intake is reported for the six minipigs surviving longer than 4.5 months post-surgery. Weight loss and reduced food intake was seen in all minipigs. After 2-3 months of weight loss, weight regain was evident in all but two minipigs which seemed to continue losing weight. Necropsy revealed some variation in the length of the alimentary, biliary and common limb between minipigs. Conclusion: The use of obese Göttingen minipigs as a translational RYGBP model is feasible and has potential for the study of RYGBP-related changes in gut function, type-2 diabetes and appetite regulation. Still, the surgical procedure is technically highly demanding in obese Göttingen minipigs and the peri-operative animal care and follow up requires close monitoring.